Pengaruh Menonton Sinetron Remaja Terhadap Cara Berpakaian Remaja di SMP Negeri 4 Padang - Kamalema, Gelsa Amanda; C, Charles; I, Iswantir; Aprison, Wedra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of increasingly advanced times means that media is developing rapidly. There are many conveniences in obtaining information from all over the world quickly, one of which is television. In television stations, many various kinds of programs are broadcast. And one of the programs most popular with teenager today is youth soap operas, this program can also be enjoyed online. Adolescents must receive special attention, so that in this research it will be known how much influence arises as a consequence of watching teenage soap operas, whether the impact is positive or negative. This influence and watching can influence one of the ways of dressing followed by the soap operas they watch. Therefore, the role of parents is very important and very influential in looking after and supervising their children so that they can dress modestly and politely according to what Islam teaches. Children cannot yet decide what is good or bad for themselves, because during adolescence they experience more difficulties during their transition period.